Are New Generations Getting Bigger in Size? Anthropometric Measurements in Erzurum. - Malkoç, ısmail; Dursun Kaya, M.; Erdoğan, Osman; Kara, Asli; Yeşilyurt, Hakki; Özkan, Behzat (Eurasian Journal of Medicine, 2014)
Objective: When the dimensional measurements of the students who spend most of their time at school are taken into consideration, inappropriate dimensions of school equipment may affect their body and psychological improvements negatively. Anthropometric measurements are necessary for designing the educational equipment of the children at school. It is emphasized that anthropometric measurements of the people living in different climate and altitude conditions w ill be different. It is mentioned that anthropometric data available for a certain region will be able to change as a result of changing socio-economical conditions and therefore, anthropometric data update is necessary at certain periods. Materials and Methods: In 2000 anthropometric data obtained from the children between the age of seven and fifteen, who were in sitting and standing positions, were measured with a repeated measurement in the same schools in 2007. Results: Mean values of the heights of elbow at standing position of the female students, 8 years old, increased from 72.38 cm in 2000 to 74.67 cm in 2007 (p<0.001). Most of the other measurements in 2007 were larger than those in 2000, giving the impression that new generation children are getting larger in size. Conclusion: As reported in the literature, anthropometric data should be updated at certain period of times.